When plasmonics meets membrane technology. (13th July 2016) - Politano, A; Cupolillo, A; Di Profio, G; Arafat, H A; Chiarello, G; Curcio, E
Abstract: In this review, we present the applications of thermoplasmonics in membrane processes. We discuss the influence of the heat capacity of the solvent, the amount of plasmonic nanoparticles in the membrane, the intensity of the light source and the transmembrane flow rate on the increase of permeability. Remarkably, thermoplasmonic effects do not involve any noticeable loss of membrane rejection. Herein, we consider application feasibilities, including application fields, requirements of feed, alternatives of light sources, promising thermoplasmonic nanoparticles and scaling up issues.